Effect of Native Oxide Layer on Mechanochemical Reaction at the GaN–Al2O3 Interface - Guo, Jian; Xiao, Chen; Gao, Jian; Liu, Jinwei; Chen, Lei; Qian, Linmao (Frontiers in Chemistry, 2021)
Mechanochemical reactions at the gallium nitride-alumina (GaN-Al2O3) interface at nanoscale offer a significant beneficial reference for the high-efficiency and low-destruction ultra-precision machining on GaN surface. Here, the mechanochemical reactions on oxide-free and oxidized GaN surfaces rubbed by the Al2O3 nanoasperity as a function of the ambient humidity were studied. Experimental results reveal that oxidized GaN exhibits a higher mechanochemical removal rate than that of oxide-free GaN over the relative humidity range of 3%–80%. The mechanical activation in the mechanochemical reactions at the GaN-Al2O3 interface is well described by the mechanically-assisted Arrhenius-type kinetics model. The analysis indicates that less external mechanical activation energy is required to initiate the mechanochemical atomic attrition on the oxidized GaN surface compared with the oxide-free GaN surface. These results may not only gain a deep understanding of the mechanochemical removal mechanism of GaN but also provide the basic knowledge for the optimization of the oxidation-assisted ultra-precision machining.